The morphological significance of the participle noun in the poetry of Abu Firas Al-Hamdani - سلوم, صفوان; أحمد, كنانة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The subject's name is derived from the various derivatives of the Arabic language, which plays an active role in performing the desired meaning, and conveying it to the recipient, by carrying different connotations that vary according to the context. and molded it from the triple and from above the triple, Then the research moved to study the morphological significance of the subject name from the triple, through several branches: (indicating occurrence, time, ratio, becoming, effectivity), and then the morphological significance of the subject name from above the triple that came in (transcendence, multiplication, participation, and accrual). , request and question). The research ended with a conclusion that included a summary of the results of the research, and proven with sources and references.